Justification of dump parameters in conditions of high water saturation of soils - Pavlychenko, Artem; Adamchuk, Andrii; Shustov, Oleksandr; Anisimov, Oleh (Technology audit and production reserves, 2020)
The object of research is the stability parameters of the massif of a single-tier dump of soft overburden rocks with a flooded slope when it is formed by a dragline excavator. One of the most problematic areas is determining the safe distance of the dragline excavator from the upper edge of the slope in the conditions of the formation of a single-tier dump of soft overburden rocks, flooded with water. The calculation of the width of the prism of possible shift was carried out using the Rocscience Slide software, which, taking into account the parameters of the slope and the physical and mechanical properties of the rock mass, automatically restores a number of curved sliding surfaces for individual safety factors. The obtained data were processed using the Microsoft Excel software, thanks to which, by the least squares method, graphs of the functions of the possible shift prism width from the height of the tier of a dump of soft overburden rocks and the level of its flooding were constructed. For the conditions of the formation of a single-tier dump of soft rocks of overburden with a height of 40–100 m and a flooding level of 0–30 m, the width of the prism of a possible shift was calculated for sliding surfaces with a safety factor of 1 and 1.2. These values are, respectively, 0–85.9 m and 0–122.6 m within the established calculation limits and depending on the method of constructing curved surfaces. The distance between the points of intersection of the horizontal surface of the tier with curved sliding surfaces with a safety factor of 1 and 1.2 is 16–52.5 m. The dependences of the width of the prism of possible shift (a) on the height of the tier of a dump of soft overburden rocks (Ho) and its level flooding (Hw), taking into account the physical and mechanical properties of the dumped mountain range, including saturated with water. The minimum deviation from the initial value of the coordinates of the points is achieved when setting the second-degree polynomial as the trend line for the function a=f(Hw), and for a=f (Hо) – a straight line. The obtained data for calculating the parameters of the possible shift prism suggest the possibility of forming a single-tier dump of soft overburden rocks with a height of 40–60 m with unloading of rock mass into the worked-out space and 70–100 m with loading the unstable part of the slope with an EK-11/70 excavator-dragline (Novokramatorsk Machine-Building plant, Ukraine).